Photophysics of Up‐Conversion Nanoparticles: Radical Photopolymerization of Multifunctional Methacrylates Comprising Blue‐ and UV‐Sensitive Photoinitiators. Issue 11 (28th October 2019) - Oprych, Dennis; Schmitz, Christian; Ley, Christian; Allonas, Xavier; Ermilov, Eugeny; Erdmann, Rainer; Strehmel, Bernd
Abstract: UCNPs based on NaYF4 :Yb 3+ /Tm 3+ @NaYF4 generate blue (450 nm, 476 nm) and UV light (345 nm, 362 nm) upon exposure with a laser emitting at 980 nm. Time‐resolved measurements indicated the same origin of the emission monitored at 362 nm and 450 nm by a rise time of 226 μs while their decay occurs with a similar time frame of 260 μs. The observation can be attributed to an energy transfer where successive absorption of three photons results in population of the 1 I 6 state. Intensity‐dependent exploration of the up‐converted emission indicated a cubic dependence between the luminescence intensity I f and laser intensity I ( I f ∝ I 3 ) monitored at 362 nm and 450 nm. The emission at 345 nm involves successive excitation with four photons. The up‐converted light excites radical photoinitiators selected from Ivocerin, thioxanthone and camphorquinone where a coinitiator, sulfonium salt, helped to generate the initiating radicals. These different systems comprising the UCNP and the photoinitiator generate crosslinked materials based on urethane dimethacrylate (M1 ) as model monomer applying laser exposure at 980 nm. Real‐time FTIR monitoring of M1 exposed indicated a different initiation time as a function of the laser intensity applied. Stress relaxation measurements complemented the understanding between material parameters on the one side and loading with UCNPs, light intensity and kinetics on the other side. Abstract : Upconversion nanoparticles (UCNPs) based on NaYF4 :Yb 3+ /Tm 3+ @NaYF4 generate blue (450 nm, 476 nm) and UV light (345 nm, 362 nm) upon exposure with a laser emitting at 980 nm. UCNPs require four photons to photopolymerize and crosslink acrylates.